Answer:
∴ The expression which is equal to 64 x 13 is (60 × 13) + (4 × 13) ⇒ C
Explanation:
The product of two numbers can be put in the form of the sum of two products by using this rule, m × n = (a × n) + (b × n), where m = a + b
Let us solve the question using this rule
∵ We need to put 64 × 13 as the sum of two products
→ Let m = 64 and n = 13
∵ m = 64 and n = 13
∵ 64 = 60 + 4
∴ a = 60 and b = 4
→ By using the rule above
∵ m × n = (a × n) + (b × n)
∵ a = 60, b = 4, and n = 13
∴ 64 × 13 = (60 × 13) + (4 × 13)
∴ The expression which is equal to 64 x 13 is (60 × 13) + (4 × 13)